Digital Twin Architecture for Autonomous Driving Validation and Verification - Kizilirmak, Orkun; Kaplan, Emre; Guzay, Cagri (2023 14th International Conference on Electrical and Electronics Engineering (ELECO), 2023)
Data-driven technologies enable emerging software solutions to blur the line between virtual and the physical systems. Digital twin is a key enabler technology to this phenomenon used primarily in the Internet of Things era. Combined with realistic user interfaces, digital twins surrogate physical systems on a virtual environment and provide time sensitive access to the physical system's parameters. By the paradigm shift towards the software-based systems in the automotive industry, digital twins can play a vital role and provides a hybrid approach for function verification and validation. In this work, we propose a digital twin architecture for abstraction and monitoring of the vehicles in order to accomplish validation and verification in a virtual environment to reduce cost and development time. Our architecture enables near real-time monitoring represented in an abstracted virtual environment and all kinds of vehicles can be represented our well-crafted software-based simulator.